Perceptions and Feedback of Undergraduate Medical Students About the Teaching and Learning Process in Pharmacology - A Question Based Study - Rajesh Kumar; Nusrat K. Bhat (Dr. Annil Mahajan, 2021)
Background: The medical undergraduate students are taught about the pathogenesis, diagnosis and pharmacotherapy of the disease in the second year of their teaching and training as per curriculum. The periodical reviewing of the teaching learning methods is very important for improvement. Purpose: To analyze the effectiveness of teaching learning methodology being followed in pharmacology subject by taking feedbacks and suggestions from the students in the form of questionnaires. Material and Methods: 150 undergraduate medical students appearing for their second professional examination were asked to fill up structured prevalidated proforma as feedback questionnaire related to the methods of teaching being followed in Pharmacology Department of Govt. Medical College, Jammu. Statistical analysis of the data was carried out using Microsoft Excel and presented as proportion. Results: All the students enrolled in the study responded to every question and gave multiple feedbacks. More than three fourth students believed that pharmacology is an interesting subject and correct knowledge of the subject is helping them in clinics and better prescription writing. 59.33% students strongly agreed with power point presentation as the most useful teaching method. Integrated teaching and case-based learning has been suggested as highly significant (86%) method to improve teaching learning whereas group discussion and inclusion of multiple-choice questions (MCQs) in the examination has been advocated by 83.33% and 80.66% students respectively. Conclusion: Power point presentation over didactic lectures, group discussion and MCQs over conventional examination methods and clinically oriented lectures were the preference of the students.